Multitarget Directed Ligand Approaches for Alzheimer’s Disease: A Comprehensive Review - Ramalakshmi, Natarajan; R.S, Remya; C.N, Nalini (Mini Reviews in Medicinal Chemistry, 2021)
Background: Alzheimer’s disease (AD) is a multifactorial neurodegenerative disease, and a drug which targets a single protein would not provide a cure for this disease. Currently available drugs for AD are all palliative rather than curative. FDA approved only five drugs for the treatment of AD, which include tacrine, donepezil, galantamine, rivastigmine, and memantine. Tacrine has been discontinued due to its hepatotoxicity. The lack of therapeutic effectiveness of the single-target drugs and multifactorial etiology of AD have led to the design of multitarget directed ligands for AD. Objective: The researchers in this field are constantly making efforts to develop a drug which may prove to be the exact cure for this disease by exploring the different biological targets associated with AD. The present review comprises various multitarget approaches and tools used for finding out a lead compound or a new drug, which will provide a cure for AD. Methods: We have scrutinized and reviewed 75 research articles published in various peer reviewed journals in the last two decades in the field of multi target directed ligand approaches for the discovery of a new therapeutic agent for AD. Results: The review highlights the recent advances in the field of AD research and shows that the battle for the discovery of an effective drug for AD is in process and AD still remains an incurable disease for which treatment is just palliative. Conclusion: The review might be helpful for researchers working on multi target directed ligands against AD.
Keywords: beta secretase